Gadolinium(III)-Loaded Nanoparticulate Zeolites as Potential High-Field MRI Contrast Agents: Relationship Between Structure and Relaxivity - Csajbók, Éva; Bányai, István; Vander Elst, Luce; Muller, Robert N.; Zhou, Wuzong; Peters, Joop A. (Chemistry : a European journal, 2005)
The effects of dealumination, pore size, and calcination on the efficiency (as expressed in the relaxivity) of Gd3+‐loaded zeolites for potential application as magnetic resonance imaging (MRI) contrast agents were studied. Partial dealumination of zeolites NaY or NaA by treatment with (NH4)2SiF6 or diluted HCl resulted in materials that, upon loading with Gd3+, had a much higher relaxivity than the corresponding non‐dealuminated materials. Analysis of the 1H NMR dispersion profiles of the various zeolites showed that this can be mainly ascribed to an increase of the amount of water inside the zeolite cavities as a result of the destruction of walls between cavities. However, the average residence time of water inside the Gd3+‐loaded cavities did not change significantly, which suggests that the windows of the Gd3+‐loaded cavities are not affected by the dealumination. Upon calcination, the Gd3+ ions moved to the small sodalite cavities and became less accessible for water, resulting in a decrease in relaxivity. The important role of diffusion for the relaxivity was demonstrated by a comparison of the relaxivity of Gd3+‐loaded zeolite NaY and NaA samples. NaA had much lower relaxivities due to the smaller pore sizes. The transversal relaxivities of the Gd3+‐doped zeolites are comparable in magnitude to the longitudinal ones at low magnetic fields (<60 MHz). However at higher fields, the transversal relaxivities steeply increased, whereas the longitudinal relaxivities decreased as field strength increased. Therefore, these materials have potential as T1 MRI contrast agents at low field, and as T2 agents at higher fields. Gd3+‐loaded dealuminated NaY zeolites have high longitudinal 1H relaxivities (r1) at about 60 MHz and high transversal relaxivities (r2) at higher fields (see graphic). Therefore, they have potential as T1 MRI contrast agents at low fields (<1 T) and as T2 contrast agents at higher fields.